Accumulation Characteristics and Hydrological Effects of Litter in Mixed Robinia pseudoacacia Plantations - CAO Zetao; DENG Yangxu; TIAN Jing; WANG Bing; LIU Guobin; YANG Yanfen (Shuitu Baochi Xuebao)
[Objective] Studying the accumulation characteristics and hydrological effects of typical mixed Robinia pseudoacacia plantations is crucial for deeply investigating the water conservation capacity of artificial forests on the Loess Plateau. [Methods] This study focused on five different mixed planting patterns of Robinia pseudoacacia in the loess hilly region, including R. pseudoacacia × Hippophae rhamnoides, R. pseudoacacia × Amorpha fruticosa, R. pseudoacacia × Pinus tabuliformis, R. pseudoacacia × Prunus davidiana, and R. pseudoacacia × Prunus sibirica, with pure R. pseudoacacia plantations serving as a control for comparative analysis. Through field investigations and laboratory experiments, quantitative research was conducted on the accumulation, water-holding capacity, and evaporation characteristics of litter in these mixed plantations. [Results] (1) The total litter accumulation in different mixed R. pseudoacacia plantations ranged from 0.29 to 1.01 kg/m2, with semi-decomposed litter accounting for more than 60% in all cases. Except for the mixture with A. fruticosa, the leaf litter accumulation in other mixtures was higher than that in pure R. pseudoacacia plantations. (2) After 24 hours, the water-holding capacity of litter from different mixtures stabilized with no significant differences. The trend for different organs was leaf > grass > fruit > branch. Furthermore, the effective interception and storage capacity of R. pseudoacacia × A. fruticosa was the largest (1.74 kg/m2), and the effective storage capacity of semi-decomposed litter was greater than that of undecomposed litter (p<0.05). (3) Evaporation of semi-decomposed and undecomposed litter reached a stable stage after 84 and 60 hours, respectively. The evaporation amount and rate followed the same trend as water-holding capacity, in the order of leaf > grass > fruit > branch. (4) During the water-holding and evaporation coupling process, a significant logarithmic relationship existed in the water-holding phase (R2≥0.84, p<0.01), while a significant power function relationship was observed in the evaporation phase (R2≥0.94, p<0.01). The natural water content of litter was reached indoors and outdoors between 48~60 hours and 24~36 hours, respectively. [Conclusion] Overall, the hydrological effect of R. pseudoacacia × A. fruticosa litter was optimal. These findings provide a scientific basis for vegetation restoration, soil and water conservation projects, and ecological benefit evaluation in the region.